Evaluation of child development of children with suspected autistic spectrum disorder - Aline Bernardes de Souza; Luzia de Miranda Meurer; Raquel Cymrot (Instituto Politécnico de Viseu, 2021)
Introduction: Child development is a continuous process of acquisition and improvement of global skills that has its main milestones in the first three years of an individual's life. Autism Spectrum Disorder (ASD) is characterized as an alteration in neurodevelopment that involves persistent deficits in communication and social interaction, in addition to stereotyped movements that can be noticed in the child's early years even before the diagnosis is defined. Objective: Analyze the overall development of children at risk for ASD in its 5 domains: cognition, communication (expressive and receptive), motor skills (fine and gross), adaptive and socio-emotional behavior, and to correlate with the indicative of ASD signs. Methods: Nine male children aged between 24 and 41 months with suspected ASD were evaluated by Protea-R (Bosa &Salles, 2018) using the Bayley child development scales (Bayley, 2018). Results: Overall, there was impairment in the 5 behaviors measured with greater intensity in children at Risk for ASD than those at Relative Risk for ASD. Cognitive, linguistic and social-emotional skills were more impaired in these. Conclusions: This study allowed reflections on the integral development of children with suspected ASD even though it was not possible to determine a pattern of global development in these individuals.